Research, development, and validation of a school leader’s resource guide for positive supports for lesbian, gay, bi-sexual, transgender (LGBT) students in schools - Kuhlmann, Kristen Lee (Kansas State University, 2014)
Providing a safe environment for LGBT students can often prove to be a controversial and difficult task, depending on the community of which the school is a part. School leaders need guidance in order to successfully help all students who are bullied. The resource guide imbedded in this dissertation was developed with guiding principles such as key issues, legal responsibilities, obstacles, and existing programs. This guide is meant to provide school leaders with additional comprehensive resources to help them provide support needed specifically for LGBT students. Only through appropriate knowledge and resources can leaders then support these students who need to be protected under basic student rights. Research, Development, and Validation of Paving the way for LGBT Students in Schools: A Road Map for Educational Leaders was developed using the research and development (R & D) methodology by Gall, Borg, and Gall (2007). The seven steps in the R & D cycle included: (1) research analysis, needs assessment, and proof of concept; (2) product planning and design; (3) preliminary product development; (4) preliminary field testing; (5) product revision; (6) main field testing; and (7) the final product revision (Gall, Borg & Gall, 2007). An analysis of the literature, needs assessment questionnaire, and proof of concept results provided information used to develop a prototype. Preliminary field testers using a rating scale and open-ended questions then evaluated the prototype. Revisions were made to the prototype based on their responses. A main field test was conducted with additional experts and final revisions were made based on feedback. Major conclusions of this study included the following: (1) school leaders need more resources to understand how to provide support for LGBT students in schools; (2) this resource guide for school leaders should include legal information, case studies, and vocabulary used with LGBT students; (3) and the R & D process produced a resource guide school leaders can use to understand their rights and responsibilities concerning LGBT Students. The resource guide‘s information includes: (1) key issues related to providing positive support for LGBT students; (2) legal responsibilities and liabilities related to providing protection for LGBT students; (3) obstacles preventing leaders from addressing the issues; and (4) existing research-based practices and field-tested model programs to help school leaders meet the challenges of support in order to provide a quality of education for these students.
Keywords: LGBT; Student support; Resource Guide; Educational leadership (0449)